posted by .

12.
(-8x) x (3x^2)

-5x^3
-24x^2
-24x^3
-5x^2

13.
(-11z)^0

z
1
-11
1

14.
14^-4

1/14^4
-56
1/14
1/14^-4

12. -24x^3
13. -1
14. 1/14

Correct

13 .
should have been +1

## Similar Questions

1. ### algebra

-12X^6+24x^5-18x^2/-6x^2=2x^4+24x^3-3x could some one check this for me please
2. ### Maths

is this correct... (3x^2+4x-3)^2-(3x^2-x+2)^2 then is it this (9x^4+24x^3-2x^2-24x+9)-(9x^4-6x^3+13x^2-4x+4) or this 9x^4+24x^3-2x^2-24x+9-9x^4-6x^3+13x^2-4x+4 should it have brakets or not that's my only problem thanks
3. ### algebra

Did I do this problem the correct way if so is there a shorter way to explain this?
4. ### math

Use polynomial long division to divide -4x^3 + 24x^2 – 24x + 4 by x^2 – 5x + 1
5. ### math help

5) Consider the equations: f(X)= -6x-1 and g(x)=4x^2 Select the solution for (f+g)(x). a) -6x -1 + 4x^2 b) -24x^3 - 4x^2 c) -24x^2 - 1 d) -6x - 1- 24x^2
6. ### alg2 check?

solve 3(8x-2)=46-2(12x+1) 24x-6=46-24x+2 24x-6=48-24x 48x-6=48 48x=42 x=42/48 or 7/8 what where the two mistakes made in the problem?
7. ### Math

consider the equations:f(x)=-6x-1 and g(x)=4x^2 Select the solution for (f+g)(x) A) -6x-1+4x^2 B) -24x^3 - 4X^2 C) -24x^2 - 1 D) -6X -1 - 24X^2 I think the answer is A. Please help
8. ### MATH

f(x)= -6x-1 and g(x)=4x^2 select the soultion for (f+g)(x) stuck not sure which answerer is correct -24x^2-1 or -24x^3-4x^2
9. ### Math

(2x-1)(3x-7)(4x+3) =6x^2-14x-33x+7 =(6x^2-19x+7)(4x+3) =24x^3+18x^2-126x+28x+21 =24x^3+18x^2-88x+21 <-- my answer but the correct answer is 24x^3-50x^2-23x+21 please correct me?
10. ### algebra

Please correct,if necessary, and simplify using long division: (-72-4x^2+8x^3-36x) devided by (x-3). My solution: 8x^2+20x+24 ------------------- 8x^3-4x^2-36x-72 8x^3-24x^2 ------------------ 20x^2-36x-72 20x^2-60x ----------------------- …

More Similar Questions